Deconstructive Humour: Subverting Mexican and Chicano Stereotypes in Un Día Sin Mexicanos (Sergio Arau 2004) - Sarah Barrow (Prof. Dr. Vittoria Borsò, Prof. Dr. Frank Leinen, Jun.-Prof. Dr. Yasmin Temelli, Prof. Dr. Guido Rings, 2012)
For a long time, US cinema developed unshakeable stereotypes of Mexican ‘otherness’, with characters of Mexican cultural and ethnic heritage stigmatised as criminals or as sensual objects of desire. Filmmakers in Mexico, meanwhile, treated Mexican Americans as misfits who belonged nowhere, or ignored them and their complex experience completely. The emergence of a distinct ‘Chicano cinema’ in the 1960s allowed for the development of a more powerful set of images of Mexican Americans, exploiting the very tool of communication that had been used against them, and for the circulation of a more productive and reflective dialogue around the questions of identity, agency and resistance that arise.